Personality development in old age relates to physical health and cognitive performance: Evidence from the Berlin Aging Study II - Mueller, S; Wagner, J; Drewelies, J; Duezel, S; Eibich, P; Specht, J; Demuth, I; Steinhagen-Thiessen, E; Gerstorf, D (Elsevier, 2016)
We examine how late-life personality development relates to overall morbidity as well as specific performance-based indicators of physical and cognitive functioning in 1,232 older adults in the Berlin Aging Study II (aged 65–88 years). Latent growth models indicated that, on average, neuroticism and conscientiousness decline over time, whereas extraversion and openness increase and agreeableness remains stable. Higher morbidity and worse grip strength were associated with higher neuroticism. Lower grip strength was further associated with lower openness, attenuated increases in extraversion, decreases in agreeableness and accelerated declines in conscientiousness. Moreover, those with poor perceptual speed reported higher neuroticism and lower conscientiousness. We also found age- and gender-differential associations between physical health and cognitive performance with levels of and changes in personality.